Assessing competitive behaviour in emerging banking market: African evidence - Doku, J.N.; Abor, J.; Adjasi, C.K.D.; Andoh, C. (Research in Accounting in Emerging Economies, 2012)
Purpose - This paper investigates competitive bank behaviour in Africa for the period 1999-2008 and further examines the impact of institutional quality and political atmosphere on competitive bank behaviour. Design/methodology/ approach - This study used panel data methodology based on the Panzar-Rosse (1987) design. Findings - The findings of the study indicates that the nature of banking system in Africa can best be described as monopolistically competitive. Also, our findings endorse the importance of institutional quality and political stability in fostering competitive banking sector. In particular, the rule of law shows positive and significant relationship with competitive bank behaviour. Additionally, the quality of regulations suggests positive association with bank competitive behaviour. With respect to political environment, stable political atmosphere is conducive for promoting competitive banking sector. Improved regulatory quality coupled with reduced level of perception about corruption fosters competitive bank behaviour. Originality/value - This paper provides useful information relevant to policy makers in the banking sector about the nature of bank competitive behaviour in Africa and the drivers behind the competitive behaviour. Copyright © 2012 by Emerald Group Publishing Limited.
Keywords: Competitive behaviour; Institutional quality; Market structure; Panzar-Rosse methodology; Political stability